2020
DOI: 10.1530/ec-20-0183
|View full text |Cite
|
Sign up to set email alerts
|

SHBG levels in primary infertile men: a critical interpretation in clinical practice

Abstract: Objective: We aimed to test the association between age, body mass index (BMI) and sex hormone-binding globulin (SHBG) in a homogenous cohort of white-European men presenting for primary couple’s infertility. Design: Retrospective study. Methods: Data from 1547 infertile men were analysed. Health-significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Fasting serum hormones were measured in every patient. Age was considered according to quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Similar to our analysis, Allen and Key reported a positive correlation between dietary fibre intake and SHBG level, as opposed to a negative correlation between animal fat consumption and SHBG 35 . Also, Boeri et al reported inverse associations between BMI and SHBG levels 94 . It can be interpreted that high‐fibre intake, low‐fat consumption and low BMI levels in vegetarians may lead to higher SHBG levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our analysis, Allen and Key reported a positive correlation between dietary fibre intake and SHBG level, as opposed to a negative correlation between animal fat consumption and SHBG 35 . Also, Boeri et al reported inverse associations between BMI and SHBG levels 94 . It can be interpreted that high‐fibre intake, low‐fat consumption and low BMI levels in vegetarians may lead to higher SHBG levels.…”
Section: Discussionsupporting
confidence: 88%
“…35 Also, Boeri et al reported inverse associations between BMI and SHBG levels. 94 It can be interpreted that high-fibre intake, low-fat consumption and low BMI levels in vegetarians may lead to higher SHBG levels. The potential role of SHBG in male fertility is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…This study has also noted a relationship between elevated serum SHBG levels and an increased risk of malnutrition in men and postmenopausal women with T2DM. Similarly, Boeri et al [ 14 ] discovered an inverse relationship between serum SHBG levels and BMI. The study observed inverse correlations between serum SHBG levels and various nutritional indices, including BMI, serum albumin, prealbumin, and transferrin, with lower levels of serum albumin, prealbumin, and transferrin, alongside higher serum SHBG levels, being indicative of the risk of malnutrition in individuals with T2DM.…”
Section: Discussionmentioning
confidence: 92%
“…It is known that there are gender-based differences in SHBG expression and premenopausal women experience fluctuations in SHBG levels during the menstrual cycle [ 13 ]. However, recent studies have shown that serum SHBG levels were linked to the nutritional status of individuals with primary infertility [ 14 ], anorexia nervosa [ 15 ], kwashiorkor [ 16 ], and polycystic ovary syndrome [ 17 ]. Notably, SHBG levels are increased in conditions such as anorexia nervosa and kwashiorkor [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…SHBG levels also increase with age; however, evidence indicates that SHBG levels decrease with increasing BMI. The observed negative correlation between BMI and SHBG levels has been reported to be stronger than the association between ageing and increased SHBG levels (Boeri et al, 2020). SHBG level, age and BMI should be considered together while evaluating the severity of male reproductive system diseases so as to improve their predictive role.…”
Section: Outlo O Kmentioning
confidence: 99%